Good Enough Governance For Poverty Alleviation Program In Village (A Case Study of Nanga Pamolontian Village) - Triadi Eka Asi Jayadiputera; Sumartono; Muhammad Nuh; Sujarwoto (JPAS (Journal of Public Administration Studies), 2023)
Scientists and public administration practitioners still find it hard to answer how to develop new institutions with limited resources. What principles must be prioritized by public managers when developing such institutions? This study aimed to answer such a question. Our case study involving new villages in remote areas of Kalimantan, Indonesia, confirmed four principles to be prioritized by public managers in implementing development programs in villages: (1) focusing on poverty alleviation, (2) being punctually oriented, (3) priority-oriented, and (4) paying attention to human resources. Focusing on poverty alleviation has the most significant proportion since it aims to achieve reformation agenda by choosing the most beneficial and relevant programs to eradicate poverty. Punctually oriented means that programs must be arranged historically based on the characteristics and conditions of the local people. Priority-oriented means sorting out programs and activities the local people truly need. Paying attention to available human resources means considering the skills and abilities of human resources to do the programs planned. Our findings confirmed that the village did not implement good enough governance (GEG) well because it did not involve the poor as workers, did not analyze the work, did not make a list of work as the priority, and did not involve the local people but people from other villages. Thus, we recommend the need for specific intervention related to policy and institutionalization so the village can run the poverty alleviation programs and community empowerment through Cash for Work Programs.